Implementation Of The School Literacy Movement (GLS) In Growing Reading Interest Of The Students - Ni Luh Ekayani; Gusti Ayu Kadek Arni Suwedawati (International Journal of Multidisciplinary Sciences, 2023)
According to some studies, reading is not very important for children in Indonesia. Students' reading interest is low, particularly in elementary schools. This is evidenced by children's lack of reading habits. The objective of this study was to determine: (1) the effectiveness of the School Literacy Movement (GLS) in fostering students' reading interest at SD Anugrah Denpasar; (2) the development of reading interest through GLS at SD Anugrah Dennpasar; and (3) the supporting and inhibiting factors of GLS in fostering students' reading interest. This study was qualitative method. Methods of data collection included observation, interviews, literature reviews, and documented studies. Data collection, data reduction, data presentation, inference, and verification methods were used to analyze the collected data. The findings of this study showed that (1) The stages of habituation, development, and learning were discussed in the context of GLS implementation. (2) Through GLS on indicators of reading interest, such as the need for reading material, actions to find reading materials, pleasure of reading material, interest in reading, and the desire to always read, students' reading interest can grow. (3) GLS supporting factors included: active participation of school members, planned programs, students, parental support, school environment, and facilities. The inhibiting factors included coordinators' consistency, the condition of the books, different interests, time allocation, and socialization.